Analysis of Factors that Influence Purchasing Decisions for Wardah Cosmetics in Pekanbaru City - Martias, Dony; Djamil, Nasrullah; Dwi Permata, Anggi (MUI Kota Pekanbaru, 2023)
The objective of this study was to identify the factors that influence consumers' decisions to purchase Wardah cosmetics in Pekanbaru city. The sample size consisted of 100 participants selected using the accidental sampling technique. This study aimed to be unbiased, clear, and concise, utilizing a formal register and precise language to ensure comprehension. The data analysis employed quantitative multiple linear regression, and the data were analyzed using the SPSS software. Based on the results of this study, it is evident that product quality has an impact on the decision to purchase Wardah cosmetics in the city of Pekanbaru. The customer's perception of prices also affects their decision to purchase the said cosmetics, as well as promotions. The independent variables, namely product quality, price perception, and promotion, have a significant impact on the dependent variable, i.e., purchasing decision, concerning Wardah Cosmetics in Pekanbaru city. The R Square value of 0.845 or 84.5% indicates that the purchasing decision is influenced by product quality, price, and promotion while 15.5% is attributable to other variables not considered in this study.